2018
DOI: 10.1080/21505594.2018.1499379
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomics of twoMycoplasma hyopneumoniaestrains andMycoplasma flocculareidentified potential porcine enzootic pneumonia determinants

Abstract: Mycoplasma hyopneumoniae and Mycoplasma flocculare are genetically similar bacteria, which coinhabit the porcine respiratory tract. These mycoplasmas share most of the known virulence factors, but, while M. hyopneumoniae causes porcine enzootic pneumonia (PEP), M. flocculare is a commensal species. To identify potential PEP determinants and provide novel insights on mycoplasma-host interactions, the whole cell proteomes of two M. hyopneumoniae strains, one pathogenic (7448) and other non-pathogenic (J), and M.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 77 publications
0
19
0
Order By: Relevance
“…It is thus of interest to better characterize the mycoplasma proteins expressed in two different growth settings mimicking aerobic and anaerobic conditions observed in vivo [64]. A number of studies have addressed the correlation between protein expression and pathogenic potential of mycoplasmas by using proteomic analysis [65] both in human (such as Mycoplasma pneumoniae [66,67], Mycoplasma genitalium [68,69] and Mycoplasma fermentans M64 [12]) and in animals (more in details Mycoplasma mobile that infects fishes [70], and Mycoplasma hypopneumoniae and Mycoplasma flocculare that are pathogenic for swines [71,72]).…”
Section: Discussionmentioning
confidence: 99%
“…It is thus of interest to better characterize the mycoplasma proteins expressed in two different growth settings mimicking aerobic and anaerobic conditions observed in vivo [64]. A number of studies have addressed the correlation between protein expression and pathogenic potential of mycoplasmas by using proteomic analysis [65] both in human (such as Mycoplasma pneumoniae [66,67], Mycoplasma genitalium [68,69] and Mycoplasma fermentans M64 [12]) and in animals (more in details Mycoplasma mobile that infects fishes [70], and Mycoplasma hypopneumoniae and Mycoplasma flocculare that are pathogenic for swines [71,72]).…”
Section: Discussionmentioning
confidence: 99%
“…The human respiratory pathogen, Mycoplasma pneumoniae , causes allergic-type inflammation by secreting the community-acquired respiratory distress syndrome (CARDS) toxin 14 , though homologues of this toxin have not been found in M. hyopneumoniae . A recent study demonstrated that M. hyopneumoniae signal peptidase I is cytotoxic to mammalian cells 15 , however this protease is not surface expressed or secreted 16,17 . While mycoplasmas can cause some direct tissue damage through the production of the metabolic by-product hydrogen peroxide 18 , this is not necessarily linked with pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Host effector molecules and their receptors are susceptible to proteolytic modifications by bacterial proteases that render them either active or inactive 20 . Despite evolving via a process of genome decay, M. hyopneumoniae has retained the genetic capacity to express several putative proteases, five of which were observed to be overrepresented in pathogenic M. hyopneumoniae strains 17 , yet how these may affect their host has not been fully explored. For example, proteolytic activity against kallikrein-kinin system substrates, such as BK, has been demonstrated in M. hyopneumoniae and other mycoplasmas, however the proteases behind this activity have only been speculated on 30,31 .…”
Section: Introductionmentioning
confidence: 99%
“…Written at the dawn of the microbial genomics era, that review was necessarily limited in general to non-specific factors affecting colonization, evasion of the host immune system, and pro-inflammatory outcomes of infection that lead to disease. Since then, the complete annotated genomes of about 70 species of mycoplasma have been published, and 4 sophisticated epigenetic (Lluch-Senar et al, 2013), transcriptomic (Madsen et al, 2008Vivancos et al, 2010;Mazin et al, 2014;Siqueira et al, 2014), proteomic (Balasubramanian et al, 2000Catrein & Herrmann, 2011;Párraga-Niño et al, 2012;Leal Zimmer et al, 2018;Paes et al, 2018) and metabolomic analyses (Maier et al, 2013;Vanyushkina et al, 2014;Lluch-Senar et al, 2015;Ferrarini et al, 2016;Masukagami et al, 2018) are now accelerating the detailed characterization of pathogenic mycoplasmas. This new dawn of post-genomic mycoplasmology is an occasion to summarize the current state of knowledge about exactly how mycoplasmas cause diseases, and what remains to be discovered through new molecular approaches.…”
Section: Introductionmentioning
confidence: 99%